EFEKTIVITAS MEDIA AUDIO VISUAL DALAM MENINGKATKAN PEMAHAMAN KONSEPTUAL DAN KETERAMPILAN PRAKTIK IBADAH SISWA PADA PEMBELAJARAN FIKIH DI MTS MANBAUL ULUM (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the effectiveness of audio-visual media in improving students’ conceptual understanding and practical worship skills in fiqh learning at MTs Manbaul Ulum Jampangtengah. The background of this study is based on the low level of students’ understanding of fiqh materials, which tend to be abstract, as well as the dominance of lecture-based teaching methods in the learning process. This study employed a qualitative approach supported by descriptive quantitative analysis. Data were collected through observation, interviews, documentation, conceptual understanding tests, and worship practice assessments involving 28 eighth-grade students. Data analysis was conducted using the interactive analysis model consisting of data reduction, data display, and conclusion drawing, supported by a comparison of students’ achievement before and after the implementation of audio-visual media. The findings show that the use of audio-visual media improved students’ conceptual understanding from an average of 61.6% to 84.6%. In addition, students’ worship practice skills increased from 60% to 87.3%. Audio-visual media helped students transform abstract concepts into more concrete understanding through visual demonstrations and systematic audio explanations. The use of this media also increased students’ attention, participation, and learning motivation, making the learning process more interactive. Therefore, audio-visual media proved to be an effective strategy in enhancing students’ conceptual understanding and worship practice skills in fiqh learning at Islamic junior high schools.